Administration of Nirsevimab for RSV Prophylaxis in Infants: A Comprehensive Review - Pan-Pan Wu; Fang-Rui Ding (Vaccines)
Respiratory syncytial virus (RSV) is the primary etiological agent responsible for lower respiratory tract infections (LRTIs) and hospitalizations among infants. Nirsevimab, a novel monoclonal antibody (mAb), offers sustained protection against RSV for a minimum of 5 months in neonates and young children. Extensive clinical trials and real-world evidence have demonstrated that nirsevimab significantly mitigates the incidence and severity of RSV infections in infants, while exhibiting favorable safety profiles and cost-effectiveness. Regulatory authorities in multiple countries have approved nirsevimab, and its implementation is progressively expanding across various healthcare settings. However, several critical issues require further attention. Specifically, a more in-depth investigation into the long-term efficacy and benefits of nirsevimab across diverse populations, particularly neonates, is essential. Additionally, accelerating the introduction and administration of nirsevimab in developing countries remains imperative. Thus, this review comprehensively summarizes the administration of nirsevimab in infants to facilitate its broader application.